2007
DOI: 10.1007/s10620-006-9679-y
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serotonin Transporter Genetic Polymorphisms and Irritable Bowel Syndrome and Its Influence on Tegaserod Treatment in Chinese Patients

Abstract: The aims of this study were to investigate the relationship of genetic polymorphisms of the serotonin reuptake transporter and the clinical subtypes of irritable bowel syndrome and its influence on the efficacy of tegaserod in Chinese irritable bowel syndrome patients with constipation. Genetic polymorphisms were analyzed in 87 patients and 96 controls, then 41 irritable bowel syndrome patients with constipation received tegaserod for 4 weeks. The primary efficacy variable was the responder rate measured by Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 30 publications
(84 reference statements)
6
56
0
2
Order By: Relevance
“…28 Regarding the association with IBS subtypes, the significant association between L/L genotype and IBS-C was shown in Chinese study. 29 Similarly to our result, in another recent meta-analysis with 3,443 IBS cases and 3,359 controls of 25 studies, the L homozygote was demonstrated to be a risk factor for IBS-C development. Moreover, L allele and L/L genotype were significantly associated with increased IBS-C risk in the East Asian population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…28 Regarding the association with IBS subtypes, the significant association between L/L genotype and IBS-C was shown in Chinese study. 29 Similarly to our result, in another recent meta-analysis with 3,443 IBS cases and 3,359 controls of 25 studies, the L homozygote was demonstrated to be a risk factor for IBS-C development. Moreover, L allele and L/L genotype were significantly associated with increased IBS-C risk in the East Asian population.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the possibility of type II error cannot be excluded in each polymorphism analysis, although there were some studies which demonstrated the genetic association with modest sample size. 12,13,29 Larger studies such as multi-center studies are needed for the accurate estimation of the genotypic risk. We did not perform the correction for multiple testing in order to reduce the likelihood that real effects would be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in individuals carrying 5-HTTLPR LL polymorphism in the SLC6A4 gene, alosetron is more effective in slowing colonic transit in patients with IBS-D [15]. Among patients with IBS-C, carriers of 5-HTTLPR LL are also less responsive to the 5-HT 4 agonist, tegaserod [16]. This example supports the benefit of applying a pharmacogenetics approach in a complex disease such as IBS.…”
Section: Genetic Variations In Drug Targetssupporting
confidence: 53%
“…This study suggests that individuals with the long allele genotype are vulnerable to develop IBS with constipation and respond poorly to tegaserod treatment [22] . Another study has shown that alosetron, a 5-HT type 3 receptor antagonist, relieves IBS-related pain and normalizes bowel function in women with diarrhea-predominant IBS.…”
Section: Serotonin Polymorphismsmentioning
confidence: 78%